Thermal Reliability Engineering in Cold Chain Logistics: Quantifying Time–Temperature Exposure, Packaging Performance, and Spoilage Risk in Distribution Networks - Somsak Kittisak Somsak Kittisak; Kanya Rattanapong Kanya Rattanapong (Kalam Practica Media, 2025)
This article presents an applied thermal reliability framework that links distribution operations to product risk using engineering metrics that can be measured and governed in practice. The framework combines (i) a time–temperature exposure model using exceedance time and mean kinetic temperature as reliability indicators, (ii) a packaging thermal performance model that represents insulation and refrigerant buffering as a transient heat transfer system, and (iii) a product degradation and spoilage risk model based on temperature-accelerated kinetics. A scenario-based quantitative study is developed for representative distribution networks including cross-docking, refrigerated line-haul, and last-mile delivery, with comparisons across packaging tiers and monitoring-control strategies. Results show that the dominant drivers of spoilage risk are not average temperature or nominal setpoints, but the upper-tail of exposure created by dwell-time uncertainty, door openings, and staging delays, and that packaging upgrades and sensor-triggered interventions reduce risk most effectively when applied to the highest-variance legs rather than uniformly across the network. The paper concludes with implementable guidance for risk-based monitoring, packaging selection, and operational governance that improves thermal reliability while controlling cost.